Cytokeratin-positive cells in the bone marrow from patients with pancreatic, periampullary malignancy and benign pancreatic disease show no prognostic information - Harald Hugenschmidt; Knut Jørgen Labori; Cathrine Brunborg; Caroline Sophie Verbeke; Lars Thomas Seeberg; Cecilie Bendigtsen Schirmer; Anne Renolen; Elin Borgen; Bjørn Naume; Gro Wiedswang (BMC Cancer, 2020)
Abstract Background Pancreatic and periampullary carcinoma are aggressive tumours where preoperative assessment is challenging. Disseminated tumour cells (DTC) in the bone marrow (BM) are associated with impaired prognosis in a variety of epithelial cancers. In a cohort of patients with presumed resectable pancreatic and periampullary carcinoma, we evaluated the frequency and the potential prognostic impact of the preoperative presence of DTC, defined as cytokeratin-positive cells detected by immunocytochemistry (ICC). Methods Preoperative BM samples from 242 patients selected for surgical resection of presumed resectable pancreatic and periampullary carcinoma from 09/2009 to 12/2014, were analysed for presence of CK-positive cells by ICC. The median observation time was 21.5 months. Overall survival (OS) and disease-free survival (DFS) were calculated by Kaplan-Meier and Cox regression analysis. Results Successful resections of malignant tumours were performed in 179 of the cases, 30 patients resected had benign pancreatic disease based on postoperative histology, and 33 were deemed inoperable intraoperatively due to advanced disease. Overall survival for patients with resected carcinoma was 21.1 months (95% CI: 18.0–24.1), for those with benign disease OS was 101 months (95% CI: 69.4–132) and for those with advanced disease OS was 8.8 months (95% CI: 4.3–13.3). The proportion of patients with detected CK-positive cells was 6/168 (3.6%) in resected malignant cases, 2/31 (6.5%) in advanced disease and 4/29 (13.8%) in benign disease. The presence of CK-positive cells was not correlated to OS or DFS, neither in the entire cohort nor in the subgroup negative for circulating tumour cells (CTC). Conclusions The results indicate that CK-positive cells may be present in both patients with malignant and benign diseases of the pancreas. Detection of CK-positive cells was not associated with differences in prognosis for the entire cohort or any of the subgroups analysed. Trial registration clinicaltrials.gov ( NCT01919151 ).